Explaining Employee Performance in Mid-Tier Hotels: The Mediating Role of Job Satisfaction between Leadership, Motivation, and Work Discipline - Rivaldo, Yandra; Moeins, Anoesyirwan; Marhalinda, Marhalinda (International Review of Management and Marketing, 2026)
Employee performance is a critical determinant of service quality and competitiveness in mid-tier hotels operating in dynamic environments. This study aims to explain employee performance by examining the effects of leadership, motivation, and work discipline, with job satisfaction positioned as a mediating mechanism. The study was conducted in mid-tier hotels in Batam City, Indonesia. The population comprised approximately 3,250 employees working in three-star hotels. Using a quantitative cross-sectional survey design, data were collected from 98 employees selected through random sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that leadership and work discipline have significant direct effects on employee performance, whereas motivation does not show a significant direct effect. However, leadership, motivation, and work discipline significantly influence job satisfaction, which in turn positively affects employee performance. Mediation analysis reveals that job satisfaction fully mediates the relationship between motivation and employee performance and partially mediates the effects of leadership and work discipline on performance. The structural model demonstrates substantial explanatory power for both job satisfaction and employee performance. These findings highlight job satisfaction as a key psychological mechanism linking managerial practices to employee performance in the hospitality industry.